Financial contracting as behavior towards risk: The corporate finance of business cycles - Krainer, Robert E. (Journal of Financial Stability, 2023)
This paper describes the balance sheet adjustments of debt and equity financed firms over time in an economy subject to taste shocks. A model is developed that describes a representative firm with a stochastic diminishing returns technology and a set of financial contracts that resolve a conflict-of-interest problem between differentially risk-averse bondholders and stockholders. The contractual resolution of this conflict-of-interest problem between the two agents is shown to shape certain stylized facts of business cycles ignored in Keynesian and Classical models. Changes in investor risk aversion and equity valuations trigger real investment decisions that can cause business cycles. Bond covenants then have the firm adjusting its financing decisions so as to offset any risk-shifting associated with the investment decisions. Stockholders manage the asset side of the firm’s balance sheet while bondholders (regulators in the case of banks) manage the financing side. In this way the welfare of both investors is coalesced over the business cycle. A similar type of analysis accounts for the age distribution of workers, and the size distribution of firms over the business cycle. Evidence presented here and elsewhere fails to reject these predictions for the U.S. non-financial and financial corporate sectors.